Zika Virus Update. Issue 4 (July 2016) - Killion, Molly M.
Abstract : The Zika virus has serious implications for pregnant women and their fetuses. Nurses must keep up-to-date on recommendations for prevention and care. As evidence about Zika virus continues to evolve, refer to the Centers for Disease Control (CDC)'s website on this topic for the latest recommendations and information: http://www.cdc.gov/zika/.